2019
DOI: 10.1038/s41598-019-49747-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Atomic Force Microscopy to Measure Thickness of Passive Film on Stainless Steel Immersed in Aqueous Solution

Abstract: Employing atomic force microscopy (AFM) to measure passive film thickness on stainless steel (SS) in aqueous solution is proposed. SUS304 austenite and SUS329J4L duplex SS samples partly covered by gold were set in a minicell. To remove the original film, the SS surface but gold was etched using dilute sulfuric acid. After cleaning, open circuit potential (OCP), and distance from the sample surface to the top of the gold were measured. They were then immersed in either 1.0% NaCl; 5.0% NaCl; or aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Many applications require steels that provide a high degree of corrosion resistance in harsh environments. For stainless steel (SS), this is facilitated by a rather thin, oxidized, passive surface region of just a couple of nanometer thickness . Its specific properties protect the surface of the alloy from corrosion attack .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many applications require steels that provide a high degree of corrosion resistance in harsh environments. For stainless steel (SS), this is facilitated by a rather thin, oxidized, passive surface region of just a couple of nanometer thickness . Its specific properties protect the surface of the alloy from corrosion attack .…”
Section: Introductionmentioning
confidence: 99%
“…For stainless steel (SS), this is facilitated by a rather thin, oxidized, passive surface region of just a couple of nanometer thickness. [8][9][10][11] Its specific properties protect the surface of the alloy from corrosion attack. [12,13] Unfortunately, the thus-achieved protection is not perfect.…”
Section: Introductionmentioning
confidence: 99%
“…From the available literature, it is reported that austenitic stainless steels in 3.5% NaCl have a passive film thickness in the range of 1–3 nm and the corrosion potential (E corr ) is almost equal to OCP. 52 The alloying elements in minor content can also have a significant effect due to the alloying composition and type of inclusions in the ASS welds by acting as locations for initiation of pits. 53…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [34][35][36] have revealed that the surfaces of passive films on stainless steel exist mainly in the form HO-M-HO and that chloride ions adsorb at certain points on the surface to form an intermediate complex 35,37 , which causes dissolution of the passive film to take place before pit nucleation. From the classical viewpoint of crystal dissolution, when the pit nucleus reaches a critical size, pit growth occurs continuously in these positions under enough chemical driving force.…”
Section: Discussionmentioning
confidence: 99%